CHEMICAL COMPOSITION OF PANICUM MAXIMUM AS AFFECTED BY PIG MANURE RATES, PLANTING METHODS AND HARVESTING STAGES IN THE NORTHERN GUINEA SAVANNA OF NIGERIA. - Idowu, Waheed; Hassan, M. R.; Tanko, R. J.; Amodu, J. T.; Adewumi, A. E.; Oyewo, T. O.; Adeleke, R. A.; Bello, S. S.; Kperum, N. T. (FUDMA JOURNAL OF SCIENCES, 2020)
Effects of Pig manure application, planting methods and harvesting stages on chemical composition of Panicum maximum were evaluated during the rainy season of 2018 at the Feed and Nutrition Research Program of the National Animal Production Research Institute, Shika, Zaria, Nigeria. The experiment was laid in a Split Plot Design with 4Ã—2Ã—3 factorial arrangement replicated three times. The manure rates were 0, 5, 10 and 15t/ha, planting methods were; drilling and broadcasting methods while the harvesting stages were 6, 9 and 12 weeks after planting. The results indicated a higher (P<0.05) (93.76%) forage dry matter (DM) at 9th week of harvest while the CP content increased (P<0.05) with increasing rate of manure application (8.46-12.62%) while there was a decline in CP content as the harvesting stage advanced (10.85-13.00%). Acid Detergent Lignin (ADL) was significantly (P<0.05) affected by pig manure rates (3.49-6.45%). Phosphorus content of the forage was significantly affected by manure application (0.11-0.17%) while the harvesting stage had a significant (P<0.05) effect on Zn, Cu and Fe with 9th week of harvest having the highest values for the micro-nutrients evaluated. It was hence concluded that the chemical composition of Panicum maximum was affected by the treatments. Therefore, pig manure can be applied at 15t/ha using broadcasting method of planting. Panicum maximum forage can be harvested at 9th week after sowing for better mineral composition in Northern Guinea Savannah of Nigeria.